2022
DOI: 10.3389/fcvm.2021.770975
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Comparisons of Aerobic Training With Different Volumes and Intensities of Physical Exercise in Patients With Hypertension: A Systematic Review and Network Meta-Analysis

Abstract: It is essential for patients with hypertension to effectively reduce and maintain appropriate blood pressure levels. As one of the non-pharmacological and invasive methods, physical exercise seems to improve blood pressure of the patients with hypertension. However, different volumes and intensities of physical exercise on the improvement of hypertension are different. To understand the effects of the type of exercise training on blood pressure and the other health status of patients with hypertension, a netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…In terms of volume, aerobic interventions involving high-volume exercise have been shown to contribute to blood pressure reduction [28,43]. However, a previous study, comparing inactive individuals with those engaging in free walking activities (characterized by very low intensity but higher volume of physical activity) did not find significant differences in SBP changes [44].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In terms of volume, aerobic interventions involving high-volume exercise have been shown to contribute to blood pressure reduction [28,43]. However, a previous study, comparing inactive individuals with those engaging in free walking activities (characterized by very low intensity but higher volume of physical activity) did not find significant differences in SBP changes [44].…”
Section: Discussionmentioning
confidence: 96%
“…PA prescription is highly recommended as an effective treatment option for all patients, including those with mild to moderate risk of elevated blood pressure [25]. Several studies have evaluated the role of exercise on SBP, DBP, and HR reduction [26][27][28], indicating that improving awareness and adherence of hypertensive patients to a healthier lifestyle, which includes dietary modifications, stress management, and PA, resulted in successful blood pressure control and enhanced response to drug therapy [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women appear to have less vasoconstriction and lower vascular resistance after exercise compared to men [46]. Lu et al [47] found that the improvement effect of moderate-high intensity exercise on male patients with hypertension was better than that of female patients. Thus, the MHPAF also contributed to the healthy blood pressure in boys.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension (HTN) is the leading preventable risk factor for cardiovascular disease (CVD) and premature death worldwide ( 1 , 2 ). The prevalence of HTN is rising globally, especially in low- and middle-income countries ( 3 ).…”
Section: Introductionmentioning
confidence: 99%